Stem Cell Therapy for the Treatment of Amyotrophic Lateral Sclerosis: Comparison of the Efficacy of Mesenchymal Stem Cells, Neural Stem Cells, and Induced Pluripotent Stem Cells - Lauren Frawley; Noam Tomer Taylor; Olivia Sivills; Ella McPhillamy; Timothy Duy To; Yibo Wu; Beek Yoke Chin; Chiew Yen Wong (Biomedicines)
Background/Objectives: Amyotrophic lateral sclerosis (ALS), or Lou Gehrig’s disease, is a debilitating, incurable neurodegenerative disorder characterised by motor neuron death in the spinal cord, brainstem, and motor cortex. With an incidence rate of about 4.42 cases per 100,000 people annually, ALS severely impacts motor function and quality of life, causing progressive muscle atrophy, spasticity, paralysis, and eventually death. The cause of ALS is largely unknown, with 90% of cases being sporadic and 10% familial. Current research targets molecular mechanisms of inflammation, excitotoxicity, aggregation-prone proteins, and proteinopathy. Methods: This review evaluates the efficacy of three stem cell types in ALS treatment: mesenchymal stem cells (MSCs), neural stem cells (NSCs), and induced pluripotent stem cells (iPSCs). Results: MSCs, derived from various tissues, show neuroprotective and regenerative qualities, with clinical trials suggesting potential benefits but limited by small sample sizes and non-randomised designs. NSCs, isolated from the fetal spinal cord or brain, demonstrate promise in animal models but face functional integration and ethical challenges. iPSCs, created by reprogramming patient-specific somatic cells, offer a novel approach by potentially replacing or supporting neurons. iPSC therapy addresses ethical issues related to embryonic stem cells but encounters challenges regarding genotoxicity and epigenetic irregularities, somatic cell sources, privacy concerns, the need for extensive clinical trials, and high reprogramming costs. Conclusions: This research is significant for advancing ALS treatment beyond symptomatic relief and modest survival extensions to actively modifying disease progression and improving patient outcomes. Successful stem cell therapies could lead to new ALS treatments, slowing motor function loss and reducing symptom severity.